Application of the effective impulse approach to stairs - Andrade, Pedro (2021)
One of the most commonly used simplified methods for predicting man induced vibrations in floors with high fundamental frequencies is the Effective Impulsive approach, first developed by the ARUP's company and later modified by the design guide SCI P354. Since the Effective Impulse approach was designed to be used in floors, its use in stairs can be arguable. To better understand the effectiveness of this method in stairs, in this paper are experimentally measured vibrations on a staircase with a poor dynamic behavior and then compared to the vibrations predicted using the Effective Impulse approach. The results indicate that this approach can be used, especially in the stair descends. The serviceability of the analyzed staircase was also verified by comparing the measured and predicted vibrations with the acceptable limits proposed by various authors and design guides.